Social entrepreneurship, microcredit and development challenges: a case study analysis of Banco Pérola - Recamonde Mendonza, Fernanda (2016)
The term 'social entrepreneurship' has been attracting growing interest from different sectors in the past years, driven by the possibility of employing business techniques to tackle recurrent social and environmental issues. At the forefront of this global phenomenon is microcredit, seen by many as an effective anti-poverty tool and having the Grameen Bank as its flagship program. While the prospects of social entrepreneurship seem promising, the newness of the concept and its somewhat confusing definition make conditions difficult to analyze this contemporary phenomenon. Therefore, the objective of this study was to discuss the challenges faced by social entrepreneurs and alternatives of development for social businesses through a case study on a Brazilian microcredit institution and inclusive business, Banco Pérola. The case addresses a growing need for case studies designed for teaching in the field of social entrepreneurship. It was focused mainly on understanding the development challenges within Banco Pérola, and built based on interviews carried out with top management, credit officer and clients of the institution, as well as on secondary data collected. An analysis of the case study was performed under a Teaching Notes. As illustrated by the Banco Pérola case, the main difficulties encountered by social entrepreneurs relate to the systematization of processes and creation of operational routines, including for performance evaluation (impact assessment tools); to the capture and management of both financial and human capital; to scaling up the business model and to the need of forging closer and more personal relationships with customers as against in traditional banking practices. In spite of certain limitations, such as the fact that the case might soon become outdated due to the fast-changing environment surrounding Banco Pérola, or the fact that not all relevant stakeholders (e.g. partners) were selected for interviews, the research objective has been achieved and the study can be seen as a contribution to spreading the concept of social entrepreneurship.